Presentation and Real-World Management of Giant Cell Arteritis (Artemis Study) - Mahr, Alfred; Hachulla, Eric; de Boysson, Hubert; Guerroui, Nassim; Héron, Emmanuel; Vinzio, Stéphane; Broner, Jonathan; Lapébie, François-Xavier; Michaud, Martin; Sailler, Laurent; Zenone, Thierry; Djerad, Mohamed; et al. (Frontiers in Medicine, 2021)
Background: Since few studies of daily practices are available on patients with giant cell arteritis (GCA), this French study aimed to describe the characteristics and management of GCA patients in a real-life setting. Methods: Cross-sectional, non-interventional, multicenter study conducted in patients ≥50 years old who consulted hospital-based specialists for GCA and were under treatment. Patient characteristics and journey, diagnostic methods and treatments were collected. Descriptive analysis was performed. Results: 306 patients (females: 67%, 74±8 years old) were recruited by 69 physicians (internists: 85%, rheumatologists: 15%); 13% had newly diagnosed GCA (diagnosis-to-visit interval <6 weeks). Overall disease duration was 13 months (IQR: 5-26). Most patients were referred by GPs (56%), ophthalmologists (10%) and neurologists (7%). Most common comorbidities were hypertension (46%), psychiatric disorders (10%), dyslipidemia (12%), diabetes (9%), and osteoporosis (6%). Initial GCA presentations included cranial symptoms (89%), constitutional symptoms (74%), PMR (48%), and/or other extra-cranial manifestations (35%). TAB, high-resolution temporal artery Doppler, 18FDG-PET, and aortic angio-CT were performed for 85%, 31%, 26% and 30% of patients, respectively. All patients received glucocorticoids which were ongoing for 89%. 29% of patients also received adjunctive medication(s) (methotrexate: 19%, tocilizumab: 15%). 40% had relapse(s), median time to first relapse: 10 months. 37% had comorbidity(ies) related to or aggravated by GCs. Conclusion: This large observational study provides insight into current medical practices for GCA. More than one third of the patients have comorbidities related to GCs for a median disease duration of 13 months. Methotrexate and tocilizumab were the most common adjunct medications.